Assessing the responses of Cladocera to a failed exploratory hydrocarbon drilling-mud sump in the Mackenzie Delta uplands (Northwest Territories, Canada) - Cheng, Elisa (2012)
Sumps act as the main form of containment and disposal method of wastes associated with exploratory hydrocarbon drilling. Leakage of drilling wastes from these sumps to the aquatic environment can be very damaging because of their toxic constituents. The purpose of the paleolimnological study is to investigate the long-term trends of a failed exploratory hydrocarbon drilling-mud sump on cladoceran assemblages. Failed sumps are expected to release drilling wastes that will increase lake water conductivity, salinity, and ionic composition. In an attempt to determine if past sump failures have affected aquatic biota, subfossil cladoceran remains were analyzed from the sediments of impacted Lake I20 and control Lake C23 in the Mackenzie Delta uplands (NT, Canada). Water was sampled to provide current water-chemistry data to compare between the two lakes. The results showed that conductivity, DOC, DIC, TDS, TSS, turbidity, and the levels of calcium, phosphorus, sodium, and sulphate in Lake I20 were still elevated compared to Lake C23. The cladocera assemblage in Lake I20 showed a distinct shift coincident with the timing of the construction and abandonment of sump Parsons F-09, suggesting that the sump might have never been successful at containing the drilling wastes. It is possible that the drilling wastes were already affecting the aquatic environment of Lake I20 at the time of sump excavation based on the stratrigraphic profile. The sedimentary record of Lake C23 showed no abrupt changes. Instead, the assemblage showed changes suggestive of climate change rather than sump disturbance. This paleolimnological study provides a better understanding of the impacts of sump activity in the Arctic aquatic ecosystems and provides initial long-term records of sump disturbance.